Effect of Educational Intervention on Promoting Adherence to Iron Supplementation Consumption Program in Pregnant Women - Somayeh Khanmohammadi; Akram Karimi-shahanjarini; Forouzan Rezapour; Maryam Farhadian (Hamadan University of Medical Sciences, 2019)
Aims: Incomplete adherence to iron supplementation consumption program is one of the main causes of iron deficiency anemia during pregnancy. The purpose of this study was to investigate the effect of educational intervention on promoting adherence to different aspects of iron supplementation consumption program in pregnant women. Materials & Methods: This semi-experimental study with pretest-posttest design with control group was conducted among 100 pregnant women during 16-20 weeks of pregnancy who referred to two health centers in Asadabad, Hamadan in 2017. The subjects were selected using random sampling method and randomly divided into intervention and control groups (50 people in each group). The training program was presented to the intervention group in the form of text messages along with pictures, self-monitoring and a phone call. Blood parameters were measured by blood tests and other variables were evaluated using a questionnaire. Data were analyzed by SPSS 21 software using Chi-square test, independent t-test and paired t-tests. Findings: Intervention could make a significant difference in the behavior of mothers in both groups regarding iron supplementation consumption with vitamin C sources (p<0.001). However, despite the improvement of iron supplementation consumption behavior, lack of simultaneous iron supplementation consumption with calcium sources and observation of the distance between tea drinking and supplement consumption, the difference between the two groups was not significant. The mothers of the two groups also had a significant difference in the amount of ferritin (p=0.003). Conclusion: The intervention program designed based on the protection motivation theory is effective in promoting adherence to the iron supplementation consumption plan and reducing anemia in pregnant women.